Antiviral RNA Recognition and Assembly by RLR Family Innate Immune Sensors - Bruns, Annie M. (Cytokine Growth Factor Rev, 2014)
Virus-encoded molecular signatures, such as cytosolic double-stranded or otherwise biochemically distinct RNA species, trigger cellular antiviral signaling. Cytoplasmic proteins recognize these non-self RNAs and activate signal transduction pathways that drive the expression of virus-induced genes, including the primary antiviral cytokine, IFNβ, and diverse direct and indirect antiviral effectors [1–4]. One important group of cytosolic RNA sensors known as the RIG-I like receptors (RLRs) is comprised of three proteins that are similar in structure and function. The RLR proteins, RIG-I, MDA5, and LGP2, share the ability to recognize nucleic acid signatures produced by virus infections and activate antiviral signaling. Emerging evidence indicates that RNA detection by RLRs culminates in the assembly of dynamic multimeric ribonucleoprotein (RNP) complexes. These RNPs can act as signaling platforms that are capable of propagating and amplifying antiviral signaling responses. Despite their common domain structures and similar abilities to induce antiviral responses, the RLRs differ in their enzymatic properties, their intrinsic abilities to recognize RNA, and their ability to assemble into filamentous complexes. This molecular specialization has enabled the RLRs to recognize and respond to diverse virus infections, and to mediate both unique and overlapping functions in immune regulation [5, 6].